The role of supply chain memory for supply chain disruption management - Alvarenga, Murilo Zamboni (2023)
Several examples demonstrate that disruptions have significant negative impacts on supply chain performance. In this context, the literature on the subject has sought to understand why some supply chains can maintain or recover their operations more quickly and effectively than others in the face of these undesirable events. Despite the advances in the topic in recent years, existing literature lacks studies addressing the role of memory in dealing with disruptive events. The beginning thesis was that memory plays an important role, directly and indirectly, in improving supply chain disruption management. However, absorbing and applying new knowledge (i.e. absorptive capacity) might be necessary to handle non-routine events such as COVID-19, considering some drawbacks that memory can bring to organizational and supply chain processes. Three papers were developed to investigate this topic. The first paper examined if both resilience and robustness are directly impacted by memory and if the relationship between these disruption management capabilities and supply chain performance is moderated by memory using a mixed-methods approach. The second explored the impact of digital technologies on supply chain resilience and robustness, considering the mediating role of memory and the moderating effect of non-routine events like the COVID-19 pandemic. Finally, the third paper investigated the moderating role of absorptive capacity in the relationship between memory and resilience and robustness. The findings contribute disruption management field showing up the role of memory in supply chain disruption management, pointing it as an antecedent, mediator, and moderator of resilience and robustness previous relationships. However, for robustness, the absorption and application of new knowledge are necessary to effectively manage non-routine events and mitigate potential drawbacks associated with memory in organizational and supply chain processes. The results demonstrate to practice the importance of learning from past disruptive events, keeping that knowledge alive, as well as acquire new knowledge in order to deal with it effectively and efficiently in the future.